The Efficacy of Materialist-Environmentalist Theory in Understanding the Incest Tabbo: Demonstrations in Specific and General Sociocultural Explanations - Leavitt, Gregory C. (Recent Research Advances in Arts and Social Studies Vol. 2, 2023)
The incest taboo has been the subject of much curiosity since the mid-19th century. While the taboo and its violation have consumed much attention especially concerning the abuse of children, other scholars have focused on the origin of the incest taboo. This focus on origin created a division between those who ascribed to Darwin’s selection theory and those who recognized environmental conditions. In the latter case what has been underdeveloped is an understanding of materialist-environmental theory as a powerful explanation for understanding complex human behaviors. In the following article I will examine the nature of materialist-environmentalism and its efficacy in explaining sociocultural evolution of human society, the specific evolution of the Hindu taboo against eating beef, and the general sociocultural evolution of the incest taboo, as powerful examples of materialist-environmental theory. In conclusion I will survey specifically the origin of the incest taboo through environmental theory.